2019
DOI: 10.1002/14651858.cd013479
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different human papillomavirus (HPV) vaccine types and dose schedules for prevention of HPV-related disease in females and males

Abstract: Cochrane Database of Systematic Reviews Comparison of di erent human papillomavirus (HPV) vaccine types and dose schedules for prevention of HPV-related disease in females and males (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 120 publications
0
99
0
11
Order By: Relevance
“…For older women who were negative for HPV types 16 and 18 there was moderate-certainty evidence that HPV vaccines reduce the risk of CIN 2+ from 45 to 14 (95% CI, 5 to 37) cases per 10,000 (2 trials, 7,552 participants) [28]. In a separate systematic review (20 trials; 31,940 participants), Bergman et al (2019) [29] found moderate-to-high certainty evidence that 2-and 3dose schedules of HPV vaccines in young females induce comparable immunogenicity, based on HPV antibody response. There was highcertainty evidence that quadrivalent and nine-valent vaccines result in similar protection against cervical, vaginal, and vulval precancers and cancers [29].…”
Section: Prophylactic Hpv Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…For older women who were negative for HPV types 16 and 18 there was moderate-certainty evidence that HPV vaccines reduce the risk of CIN 2+ from 45 to 14 (95% CI, 5 to 37) cases per 10,000 (2 trials, 7,552 participants) [28]. In a separate systematic review (20 trials; 31,940 participants), Bergman et al (2019) [29] found moderate-to-high certainty evidence that 2-and 3dose schedules of HPV vaccines in young females induce comparable immunogenicity, based on HPV antibody response. There was highcertainty evidence that quadrivalent and nine-valent vaccines result in similar protection against cervical, vaginal, and vulval precancers and cancers [29].…”
Section: Prophylactic Hpv Vaccinationmentioning
confidence: 99%
“…In a separate systematic review (20 trials; 31,940 participants), Bergman et al (2019) [29] found moderate-to-high certainty evidence that 2-and 3dose schedules of HPV vaccines in young females induce comparable immunogenicity, based on HPV antibody response. There was highcertainty evidence that quadrivalent and nine-valent vaccines result in similar protection against cervical, vaginal, and vulval precancers and cancers [29].…”
Section: Prophylactic Hpv Vaccinationmentioning
confidence: 99%
“…Better antibody response in terms of higher GMT is seen when there is a longer interval between twodoses (12 months) than shorter interval (6 months) up to 3 years follow-up. 37 Therefore, inadvertent delays due to non-availability of vaccine, patient factors, etc. should not be a cause of concern.…”
Section: Interrupted Dosage Schedulementioning
confidence: 99%
“…The recent development of a highly effective vaccine against the human papillomavirus (HPV) has been met with widespread clinical and public health interest and awareness based on scientific and lay literature reports of its effectiveness and resulting reductions in associated cancer risk [1][2][3][4]. Systematic reviews of randomized controlled trials (RCT) revealed strong antibody responses from two-and three-dose vaccinations that have resulted in a significant reduction in the incidence of external genital lesions and will likely result in long-term reduction in the incidence of high-risk cervical cancers and other HPV-mediated pathologies [5][6][7]. Recent systematic reviews and meta-analyses have revealed compelling evidence of substantial reductions in HPV-specific infections in geographic areas with high vaccination coverage, which will likely facilitate both direct clinical protection and more far-reaching effects involving herd immunity within those communities [8,9].…”
Section: Introductionmentioning
confidence: 99%